Kinesin family member 6 (kif6) is necessary for spine development in zebrafish. Issue 12 (20th October 2014) - Buchan, Jillian G.; Gray, Ryan S.; Gansner, John M.; Alvarado, David M.; Burgert, Lydia; Gitlin, Jonathan D.; Gurnett, Christina A.; Goldsmith, Matthew I.
<x xml:space="preserve">Abstract</x> Background: Idiopathic scoliosis is a form of spinal deformity that affects 2–3% of children and results in curvature of the spine without structural defects of the vertebral units. The pathogenesis of idiopathic scoliosis remains poorly understood, in part due to the lack of a relevant animal model. Results: We performed a forward mutagenesis screen in zebrafish to identify new models for idiopathic scoliosis. We isolated a recessive zebrafish mutant, called skolios, which develops isolated spinal curvature that arises independent of vertebral malformations. Using meiotic mapping and whole genome sequencing, we identified a nonsense mutation in kinesin family member 6 (kif6gw326) unique to skolios mutants. Three additional kif6 frameshift alleles (gw327, gw328, gw329) were generated with transcription activator‐like effector nucleases (TALENs). Zebrafish homozygous or compound heterozygous for kif6 frameshift mutations developed a scoliosis phenotype indistinguishable from skolios mutants, confirming that skolios is caused by the loss of kif6. Although kif6 may play a role in cilia, no evidence for cilia dysfunction was seen in kif6gw326 mutants. Conclusions: Overall, these findings demonstrate a novel role for kif6 in spinal development and identify a new candidate gene for human idiopathic scoliosis. Developmental Dynamics 243:1646–1657, 2014. © 2014 Wiley Periodicals, Inc.